ANALYSIS OF THE LEGISLATION OF SOME FOREIGN COUNTRIES TO FIGHT AGAINST TERRORISM (Proceedings of International Educators Conference, 2024)
Religious extremism and terrorism were major global concerns in the late 20th and early 21st centuries, when they emerged as the most potent threats to social order and political stability1. The spread of threats and hazards, deliberate killing, invasion, international terrorism, religious extremism, illegal immigration, human trafficking, and foreign ideas among young people nowadays create new challenges for internal affairs organizations to stop and eradicate in a timely manner.